Эколого-фаунистические исследования кровососущих комаров (Diptera, Culicinae) на Украине - Шевченко, А.К. (Вестник зоологии, 1968)
Culicinae in the Ukraine are represented by 52 species and 8 subspecies. The article gives their distribution within the republic and brief zoogeographical analysis. The classification and characteristic of Culicinae reproduction places are presented. They are divided into three groups: constant, periodically existing and temporary reservoirs. The relativity of the concepts «anthropophility» and «exophilityo is shown on the example of various genera and species. In mosquitoes Culex pipiens pipiens both these populations are present. But nowadays in some big cities the conditions are favourable for sharp increase of the anthropophilous population of Culex pipiens pipiens.